FRENCH-ROMANIAN WORKSHOP “PROMOTING GREEN CHEMISTRY” 06 – 07 JULY 2010 – ORLEANS, FRANCE - Irina-Claudia Alexa (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
The French-Romanian Workshop "Promotion of Green Chemistry - Applications in Organic Synthesis, Analytical Chemistry and Process Engineering" organized by the Research Center “Applied Chemistry and Process Engineering” of the "Vasile Alecsandri" University from Bacău (Romania) and the Institute of Organic and Analytical Chemistry, University of Orleans (France), took place on 6-7 July, 2010 in Orleans. The workshop was attended by 32 researchers, 16 from France and 16 from Romania.